AN EXPERIMENTAL STUDY ON HEAT AND MASS TRANSFER FOR CLOSED WET COOLING TOWER USING DIFFERENT WATER DISTRIBUTION SYSTEMS - Saleh Mahdi, Qasim; Mohammad Jaffal, Hayder (Journal of Engineering and Sustainable Development, 2016)
The aim of this research is to investigate experimentally heat and mass transfer characteristics of the modified Closed Wet Cooling Tower (CWCT) using different water distribution systems. A prototype of forced draft counter flow CWCT modified with added packing was designed, manufactured and tested for cooling capacity of 9 kW in Iraq. A series of experiments have been conducted for different operational parameters on thermal performance of CWCT with packing located under heat exchanger .To get a best performance of the nozzles, a comparative work had been applied for three types of spray water nozzles: jet, swirl and threaded. The results indicated that the suitable spray nozzle is the key aspect to enhance the thermal performance of the tower. Furthermore, it is found that swirl and jet types spray nozzle have more significant enhancement than threated type spray nozzle. So, the best performance for swirl type spray nozzle. For same operating conditions, it is found that over (7%) and (13%) enhancement of cooling capacity in swirl type than jet and threated types, respectively.